Circuit analysis theory and practice - Robbins, Allan H.; Miller, Wilhelm (Delmar Cengage Learning, 2007)
Written for electronics engineering technology students taking their first course in circuit theory, this exceptional book has been hailed by users and reviewers alike as one of the best on the market. The 4th Edition provides updated coverage of standard circuit analysis topics in a remarkably easy-to-understand fashion, including fundamentals of DC and AC, methods of analysis, capacitance, inductance, magnetism, simple transients, transformers, Fourier series, and more. Essential concepts are complemented with hundreds of worked out examples designed to lead readers through the critical thinking processes required to solve problems, preparing them to reason their way through life-like situations expected to be encountered on the job.